Evone® Flow-Controlled Ventilation During Upper Airway Surgery: A Clinical Feasibility Study and Safety Assessment - Meulemans, Jeroen; Jans, Alexander; Vermeulen, Kristien; Vandommele, Johan; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Surgery, 2020)
Introduction: During upper airway surgery in a narrowed airway due to tumor or stenosis, safe ventilation, good laryngotracheal exposure and preservation of an adequate surgical working space is of paramount importance. This can be achieved by small-lumen ventilation such as High Frequency Jet Ventilation (HFJV). However, this technique has major drawbacks, such as air-trapping and desaturation in patients with poor pulmonary reserve. Recently, an innovative ventilating system with flow-controlled ventilation (FCV) and a small-lumen endotracheal tube, the Evone® (Ventinova, Eindhoven, The Netherlands), was introduced, claiming to counter the drawbacks of HFJV. Objectives: To evaluate feasibility and safety of the Evone® FCV system in difficult upper airway surgery and to critically appraise this novel ventilation method . Patients & methods: Evone® is a FCV-device using a small-bore cuffed tube (Tritube®). This ventilator actively sucks air out of the lungs, rather than relying on the passive backflow of air like in HFJV. Data related to the medical history, surgery and anesthesia of all consecutive patients undergoing upper airway surgery with Evone® FCV ventilation were included in a tertiary center retrospective observational study. Results: 15 Patients, with a median age of 54 years, were included. Surgical procedures and indications included laser-assisted endoscopic treatment of idiopathic subglottic stenosis (n=3), tracheal stenosis (n=1) and posterior glottic stenosis (n=2), biopsy and/or Transoral Laser Microsurgery for laryngeal (pre)malignancy (n=7) and resection of benign lesions with posterior (supra)glottic location (n=2). Mean ventilation duration was 52.0 min (range 30-115 min, SD 19.6 min), mean surgery duration was 31.7 min (range 15-65 min, SD 13.2 min), mean minimal SaO2 was 96.3% (range 89-100%, SD 4.0%) and mean peak pCO2 was 41.4 mmHg (range 31-50 mmHg, SD=5.5 mmHg). No anesthesia- or surgery-related complications, adverse events or intra-operative difficulties were reported during or after any of the 15 procedures. In all cases, compared to HFJV, Evone® FCV ventilation allowed a superior visualization and working space during the surgical procedure. Conclusion: The Evone® FCV ventilation system provides excellent conditions in patients undergoing upper airway surgery, as it combines excellent accessibility and visibility of the operation site with safe and stable ventilation.